Sistem Pengaturan Izin Tempat Penjualan Minuman Beralkohol (Studi Perda Kota Kendari No. 3 Tahun 2015 Tentang Retribusi Izin Tempat Penjualan Minuman Beralkohol) - Israti La Taa; Ahmadi Ahmadi; Aris Nur Qadar Ar. Razak (Institut Agama Islam (IAIN) Kendari, 2022)
Abstract: The purpose of this study is to find out how the mechanism for granting a permit for selling alcoholic beverages based on the Kendari City Regional Regulation no. 3 of 2015 concerning levies for permits for selling alcoholic beverages and to find out the factors and efforts that hinder the Kendari City government in implementing Kendari City Regional Regulation No. 3 of 2015. This study uses a qualitative research type with an empirical normative typology that focuses on the study of Regional Regulations and empirical data in the field using a legislative approach, a conceptual approach and a case approach. Data collection techniques using interview, documentation and observation techniques.The results of the study indicate that the mechanism for granting permits for selling alcoholic beverages goes through several stages and processes based on the legislation, but the system for granting permits for selling alcoholic beverages is still experiencing several obstacles due to factors, namely: the Kendari City Government is not thorough and does not update permits for sellers of alcoholic drinks suspected of violating the provisions of regional regulations, lack of law enforcement officers, administrative systems that are still manual and differences of opinion and understanding. So that to optimize its implementation, the Kendari City government makes efforts, namely: updating permits and being careful when reviewing locations, increasing human resources in terms of enforcing regional regulations, including detailed spatial plans in the OSS application. Keywords: Licensing System, Regional Regulations, Alcoholic Drinks.